Pengaruh Supervisi Akademik, Iklim Kerja dan Motivasi Berprestasi terhadap Kinerja Guru SMP Kecamatan Banjarmasin Utara: The Influence of Academic Supervision, Work Climate and Achievement Motivation on the Performance of Junior High School Teachers in North Banjarmasin District - Noor Hariani; M. Saleh; Metroyadi Metroyadi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This research is motivated by the still low performance of teachers in Junior High Schools in the North Banjarmasin District. The results of the preliminary study revealed that many teachers' performance is still low, as evidenced by the quality of their work results, which are not optimal. This research is a descriptive, quantitative study. The study population was 265 Junior High School teachers in North Banjarmasin District, with a sample of 160 selected using Proportional Random Sampling. Data were collected through questionnaires and then analyzed using descriptive and inferential statistics using SPSS 26. The results of the study show: 1) Academic supervision of the principal, work climate, achievement motivation and teacher performance are classified as high. 2) There is a direct influence of academic supervision of the principal on teacher performance; work climate on teacher performance; achievement motivation on teacher performance; academic supervision of the principal on achievement motivation; work climate on achievement motivation.3) There is an indirect influence of academic supervision of the principal on teacher performance through achievement motivation. There is an indirect influence of work climate on teacher performance through achievement motivation. Academic supervision of the principal and the work climate have direct and indirect effects on teacher performance through teacher achievement motivation. Teachers should always be careful in their work, increase their motivation to achieve, nd always complete tasks according to SOP.